Integrating Sharia Values into Education in Aceh: A Qualitative Case Study of Policy, Curriculum, and Pedagogical Practice - Irwandi Irwandi; Nurmalina Nurmalina; Fakhrul Rijal (STAI Hubbulwathan Duri, 2025)
Aceh, the only province in Indonesia with special autonomy to enforce Islamic law, offers a unique context for examining the integration of Sharia values into public education. This study explores how Islamic principles are embedded into educational policy, curriculum, and teaching practices within the region. A qualitative case study approach was employed, involving in-depth interviews with government officials, school principals, and teachers. Data collection also included analysis of regional policy documents, school curricula, and instructional materials to understand how Sharia values are implemented. Findings reveal that Sharia values are formally institutionalized in regional education policies, which require the incorporation of Islamic teachings not only in religious subjects but across secular disciplines. Pedagogical approaches emphasize character building, discipline, and the internalization of Islamic ethics, with educators expected to model moral behavior. However, implementation is uneven. Challenges include inconsistent teacher understanding of Sharia-based education, insufficient curricular resources, and tension between local religious expectations and national education standards. Despite these challenges, stakeholders perceive the integration as a valuable means of preserving Acehnese Islamic identity while promoting moral education within the broader national curriculum. The study underscores the nuanced balance required to align regional religious norms with national educational objectives. This research contributes to discussions on religion and education by highlighting both the promise and complexity of embedding localized religious values into public schooling within an autonomous framework.